Climate Change as Environmental International Security Issue: The Threat of Global Warming in Small Island States - Santos, Letícia Britto dos (Conjuntura internacional, 2015)
This paper discusses the process of securitization of climate change. The Intergovernmental Panel on Climate Change (IPCC) is seen as a securitizer agent and the Small Island States as an audience. The possibility of those countries disappearing is a threat to the national and the human security.